Efeito do tipo de sedimento, habitat e competição sobre o estabelecimento de uma espécie de macrófita submersa nativa (Egeria najas) e uma exótica (Hydrilla verticillata) na planície de inundação do alto rio Paraná - Silveira, Márcio José da (2009)
Colonization and competition are key mechanisms in spatial and temporal dynamics of communities. Currently, alien species have invaded many ecosystems, affecting native plants and changing ecological processes. This study of apical shoots of three species of Hydrocharitaceae: Egeria najas, E. densa and Hydrilla verticillata. The shoots were left to dry on clay or sand from zero to four days, and were then returned to aquaria containing water. To approximate natural conditions, the aquaria containing clay had higher turbidity and nutrient (P and N) concentrations than did the aquaria with sand. Evaluated the potential for establishment and competition of submerged macrophytes H. verticillata (exotic), together with the native E. najas. Fragments were planted in pots and left in two environments (in the main channel of the Paraná River and in a lake) for 30 days. These species were also planted in tanks and subjected to a competition experiment, using the additive method, with constant density of H. verticillata E. najas been considered the target species. All species dried faster on sand substrate, which led to lower regeneration (in terms of dry weight, length, sprout and root formation)in this treatment. H. verticillata fragments elongated faster than the other species, but E. najas was the most successful species (in terms of increase in dry weight) in the sand treatment. Our results indicate exotic H. verticillata has a competitive advantage, at least in its early stages of regeneration, over the other two, native species, especially in more eutrophic and turbid habitats; whereas E. najas fragments have a competitive advantage in less-turbid, oligotrophic and sand-dominated sites. The results obtained in situ showed that E. najas had a better performance than H. verticillata in both habitats. However, in the tanks there was a significant negative relationship between the density of H. verticillata and the biomass of E. najas, showing high competitive potential of the first species. Experiments carried out in situ are in accordance with the distribution of E. najas which prefers lentic habitats, while the competition experiment indicates that E. najas may be displaced by the exotic species when both colonize the same sites.